Eyebrow Reconstruction Using a Composite Skin Graft from Sideburns. Issue 1 (January 2015) - Matsuda, Ken; Shibata, Minoru; Kanazawa, Shigeyuki; Kubo, Tateki; Hosokawa, Ko
<x xml:space="preserve">Abstract</x> Summary: Wide resection of malignant skin tumors in the upper orbital region often results in soft-tissue defects involving the eyebrow. We used composite skin grafts from the area around the sideburns for 1-stage reconstruction of skin and eyebrow defects. The results were aesthetically satisfying because the hair and shape of these regions were similar to those of the original eyebrow, and donor-site closure was easy with inconspicuous scar. The survival of full-thickness skin graft area of composite grafts from sideburn facilitates revascularization of thicker hair follicles in the graft and allows safe, natural eyebrow reconstruction.